Assessing the bioaccumulation and translocation potential of vetiver grass for dioxins phytoremediation in Bien Hoa airbase, Viet Nam - Nguyen, Thi Thanh Thao; Nguyen Quoc Dinh,; Martine Leermakers,; Yue Gao,; Dinh Van Huy,; Nguyen Thi Loi,; Ngo, Thi Thuy Huong (Vietnam Journal of Science and Technology, 2025)
Dioxins (PCDD/Fs) are well-known toxic organic pollutants that accumulate in the environment and the food chain, imposing a risk to human health and the ecosystem. Due to the use of dioxin-contaminated herbicides during the US-Vietnam War, there are several hotspots in Vietnam with very high levels of dioxins. Phytoremediation has been increasingly developed in recent decades because of its low cost and environmental-friendly aspect. Vetiver grass is a plant that can remediate both organic and inorganic agents. In this study, the uptake and translocation of dioxins in Vetiver grass (Chrysopogon zizanioides) from the dioxin-contaminated soil was investigated in a field experiment on the Bien Hoa airbase, Vietnam. An experimental area was divided into six plots, of which three were planted with Vetiver grass and three served as control plots, with the initial dioxin concentrations as following: FC2>FC3>FC1>FT2>FT3>FT1.Vetiver grass had grown well on the dioxin-contaminated soils, yielding high biomass and the level of dioxins in the roots of vetiver grass was positively correlated (r2 = 0.67; p<0.01) with its growth rate. During the first year of cultivation, Vetiver grass had the greatest capacity to efficiently accumulate dioxin. Accumulation occurs in the roots, with BAF>1 throughout the entire experiment period for FT3, and in the first year for FT1 and FT2. The dioxin translocation from the roots to the shoots was significantly lower than the BAF and less than one (TF<1), with the first and second sampling times having the highest values compared to the others. Dioxin concentrations do not provide a reliable indicator of its bioavailability but numerous other factors, such as physicochemical properties of the soil and microbes. Our study aims to contribute significant insights to capability of Vetiver grass to accumulate and translocate dioxins, hence the arsenal of dioxin remediation. Furthermore, we envisage translating our findings into practical applications in other areas, considering optimized planting techniques, growth conditions, and long-term sustainability.